2014
DOI: 10.1120/jacmp.v15i6.4663
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective tomotherapy image‐guidance study: analysis of more than 9,000 MVCT scans for ten different tumor sites

Abstract: The purpose of this study was to quantify the systematic and random errors for various disease sites when daily MVCT scans are acquired, and to analyze alternative off‐line verification protocols (OVP) with respect to the patient setup accuracy achieved. Alignment data from 389 patients (9,418 fractions) treated at ten different anatomic sites with daily image‐guidance (IG) on a helical tomotherapy unit were analyzed. Moreover, six OVP were retrospectively evaluated. For each OVP, the frequency of the residual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…The breast target volume extends from skin surface to the chest wall and lung interface. Affected by respiratory motion, it accounted to an unavoidable setup error of 3 mm 20 . To reduce the radiation dose, some studies suggested first three fractions or alternate-day imaging protocol 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The breast target volume extends from skin surface to the chest wall and lung interface. Affected by respiratory motion, it accounted to an unavoidable setup error of 3 mm 20 . To reduce the radiation dose, some studies suggested first three fractions or alternate-day imaging protocol 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Affected by respiratory motion, it accounted to an unavoidable setup error of 3 mm. 20 To reduce the radiation dose, some studies suggested first three fractions or alternateday imaging protocol. 21 Nevertheless, Goddu et al observed significant dose differences of 11-mm shifts in the anterolateral and 3-mm shifts in the posteromedial directions if patient setup errors remained uncorrected in helical tomotherapy treatments, leading to dose reduction in target volume.…”
Section: Recommendation On Imaging Protocolmentioning
confidence: 99%
“…It would be useful to compare the information provided by the images according to the various acquisition modes and to be able to choose, in a objective way, the most adapted IGRT protocol (frequency and mode) in order to limit the received doses while improving the quality of treatments (5,8,15,17) …”
Section: Discussionmentioning
confidence: 99%
“…Image‐guided radiotherapy (IGRT) allows us to take into account not only patient positioning and target localization, but also structure avoidance and morphological variations (1,2,3,4,5,6) . Different possibilities have been described to take into account patient management (7,8) . In order to have a comprehensive approach to the total delivered dose, it is important to evaluate these imaging doses during treatment procedures especially when these techniques are used frequently.…”
Section: Introductionmentioning
confidence: 99%
“…Megavoltage CT (MVCT) is used in different tumour sites as a daily IGRT technique to quantify systematic and random errors. 63 Johnson et al 64 used daily MVCT to analyse the interfraction variation of the stomach position in gastric lymphoma. Aggarwal et al 65 assessed the use of tomotherapy with MVCT to estimate the internal target volume of gastric tumours and showed that the target changes widely during the course of radiation treatment, and severe target displacements were observed.…”
Section: Interfractional Motionmentioning
confidence: 99%